PERAN MANAJEMEN SUMBER DAYA MANUSIA DALAM MENINGKATKAN KINERJA KARYAWAN PT BRINGIN GIGANTARA - Sami, Nanang; Islamuddin, Islamuddin (JURNAL MANAJEMEN MODAL INSANI DAN BISNIS (JMMIB), 2024)
This research focuses on the role of HR management in improving employee performance at PT Bringin Gigantara, a company engaged in Cash Management Services. The company carries out HR development through education and training tailored to the needs and job types of employees. Performance assessment is conducted using qualitative methods involving evaluation of employee behavior and personality. The results of the research show that PT Bringin Gigantara implements a structured method to measure the quantity and quality of work, as well as employee punctuality. Work quantity measurement involves agreed-upon targets and routine evaluations. Work quality is assessed based on high standards covering various aspects, and punctuality is monitored through a digital time-tracking system. HR management in this company plays a significant role in supporting employees to achieve their targets through training, incentives, and efficient workload management. The conclusion of this research is that PT Bringin Gigantara has successfully created a productive work environment and motivated employees through effective HR management, high work quality standards, and a measured approach to ensuring punctuality.Keywords: Employee Performance, Human Resources management.